2023
DOI: 10.1177/24730114231171117
|View full text |Cite
|
Sign up to set email alerts
|

A New Trend in Social Media and Medicine: The Poor Quality of Videos Related to Ankle Sprain Exercises on TikTok

Abstract: Background: Social media platforms, like TikTok, have become popular options for the distribution of health care information. Because of the lack of scientific oversight, the quality of health care–related videos has become a focus of the current literature. However, orthopaedic surgery has lagged behind other fields in acknowledging the widespread utilization of TikTok videos for medical information consumption. This study aims to assess the quality and educational benefits of ankle sprain–related TikTok vide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…In this study, the proportion of certi ed orthopedic physicians (36.0%) and senior professional titles (29.6%) on rst 25 results were pretty unsatisfactory. One study showed that the low-quality content could be easily accessible on TikTok [31]. In this study, compared with the other two platforms, TikTok has a signi cantly higher proportion of certi ed orthopedic physicians (77.6%) and senior professional titles (69.2%), which may be attributed to the audit mechanism of TikTok, only allowing certi ed doctors to upload professional medical videos [32].…”
Section: Major Ndingmentioning
confidence: 77%
See 1 more Smart Citation
“…In this study, the proportion of certi ed orthopedic physicians (36.0%) and senior professional titles (29.6%) on rst 25 results were pretty unsatisfactory. One study showed that the low-quality content could be easily accessible on TikTok [31]. In this study, compared with the other two platforms, TikTok has a signi cantly higher proportion of certi ed orthopedic physicians (77.6%) and senior professional titles (69.2%), which may be attributed to the audit mechanism of TikTok, only allowing certi ed doctors to upload professional medical videos [32].…”
Section: Major Ndingmentioning
confidence: 77%
“…The total DISCERN score was calculated by summing up scores over questions 1-15. All videos were divided into ve categories based on their total DISCERN score: very poor (< 27), poor (27)(28)(29)(30)(31)(32)(33)(34)(35)(36), fair (39-50), good (51-62), and excellent (63-75). JAMA benchmark criteria were used to evaluate online health information reliability, including four criteria (authorship, attribution, disclosure, and currency).…”
Section: Methodsmentioning
confidence: 99%
“…assessed the quality and educational benefits of ankle sprain-related TikTok videos and confirmed that the educational value of the videos related to ankle sprain injury exercises was poor. With only 2% of videos receiving a grade of “fair” and no videos reaching a score of “good” or “excellent,” health care professionals should be aware of the low-quality content easily accessible on TikTok [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not all videos contained treatment information; however, according to the DISCERN tool manual, content related to personal care measures for myopia prevention, such as increasing outdoor activities and reducing near work time, should be considered therapeutic intervention and be included in the treatment choice domain. Total DISCERN quality was classified as very poor (< 26), poor (27–38), fair (39–50), good (51–62), and excellent (63–80) [ 17 , 22 , 24 ].…”
Section: Quality Assessmentmentioning
confidence: 99%